Stenotrophomonas maltophilia: An uncommon cause of liver abscess - Mohanty, Srujana (IDCases, 2021)
We report an uncommon case of pyogenic liver abscess due to Stenotrophomonas maltophilia in an apparently immune-competent individual, the timely recognition of which could avoid a potentially fatal course of infection in the patient. A 45-year-old man, with history of moderate alcohol intake since the last 10 years, was admitted with intense right-sided upper abdominal pain and right-sided chest pain of 10-days duration. Culture of the ultrasound-guided liver aspirate sample yielded a pure growth of S. maltophilia identified by the VITEK-2™ automated microbial identification system. Treatment with parenteral levofloxacin and oral trimethoprim-sulfamethoxazole along with pigtail catheter drainage and other appropriate supportive management led to resolution of the abscess with no recurrence of infection at two months follow-up. Physicians need to be aware that S. maltophilia infections may not be restricted to hospitalized patients as a low-virulence opportunistic pathogen, but may occur as an important emerging pathogen in community-acquired infections as well.